Imaging of neutral lipids by oil red O for analyzing the metabolic status in health and disease - Mehlem, Annika; Hagberg, Carolina E; Muhl, Lars; Eriksson, Ulf; Falkevall, Annelie (Nature protocols, 2013)
Excess lipid accumulation in peripheral tissues is a key feature of many metabolic diseases. Therefore, techniques for imaging and quantifying lipids in various tissues are important for understanding and evaluating the overall metabolic status of a research subject. Here we present a protocol that detects neutral lipids and lipid droplet (LD) morphology by oil red O (ORO) staining of sections from frozen tissues. The method allows for easy estimation of tissue lipid content and distribution using only basic laboratory and computer equipment. Furthermore, the procedure described here is well suited for the comparison of different metabolically challenged animal models. As an example, we include data on muscular and hepatic lipid accumulation in diet-induced and genetically induced diabetic mice. The experimental description presents details for optimal staining of lipids using ORO, including tissue collection, sectioning, staining, imaging and measurements of tissue lipids, in a time frame of less than 2 d.